Emergency inguinal hernia repair under local anesthesia: a 5-year experience in a teaching hospital. Issue 1 (December 2015) - Chen, Tao; Zhang, Yunhe; Wang, Haolu; Ni, Qihong; Yang, Linhua; Li, Qiwei; Wang, Jian
Abstract Background Local anesthesia (LA) has been reported to be the best choice for elective open inguinal hernia repair because it is cost efficient, with less post-operative pain and enables more rapid recovery. However, the role of LA in emergency inguinal hernia repair is still controversial. The aim of this study is to investigate the safety and effectiveness of LA in emergency inguinal hernia repair. Methods All patients underwent emergency inguinal hernia repair in our hospital between January 2010 and April 2014 were analyzed retrospectively in this study. Patients were divided into LA and general anesthesia (GA) group according to the general conditions of the patients decided by anesthetists and surgeons. The outcome parameters measured included time to recovery, early and late postoperative complications, total expense and recurrence. Results This study included a total of 90 patients from 2010 to 2015. 32 patients (35.6 %) were performed under LA, and 58 (64.4 %) were performed under GA. LA group has less cardiac complications (P = 0.044) and respiratory complications (P = 0.027), shorter ICU stay (P = 0.035) and hospital stay (P = 0.001), lower cost (P = 0.000) and faster recovery time (P = 0.000) than GA group. Conclusion LA could provide effective anesthesia and patient safety in emergency inguinal hernia repair.